THE SURFACE EXPRESSION OF ALPHA GRANULE PROTEINS FOLLOWING THROMBIN STIMULATION - Gralnick, H R; Magurder, L M; Hansmann, K; Vail, M; Marti, G; McEver, R; Williams, S (Thrombosis and Haemostasis, 1987)
We have studied the platelet glycoproteins (GP) GPIb and the GPIIb/IIIa and the expression of alpha granule proteins (AGP) on the platelet (P) surface following thrombin (T) stimulation. The platelets were separated from plasma proteins on a arabinogalactan gradient. The P were stimulated with purified alpha T 0.1u/108p. Either monospecific polyclonal or murine monoclonal antibodies were used to detect the P glycoprotein and AGP. The platelets were analyzed on an EPICS V Flow Cytometer. Resting P had small amounts of AGP (2-8%) present on their surface. Within 1-3 min. after T stimulation significantly increased amounts of PF4 (26%) vWf (8%) Ig (10%) and the 140 kD alpha granule membrane (70%) were present on the P surface. The peak expression of all the AGP occurred within 5 mins. The 140 kD activation protein remained stable over 3-60 mins, in contrast the PF4 and the vWf expression peaked at 5 mins. and then decreased to near baseline levels. The GPIb and GPIIb/IIIa showed different patterns after activation. The GPIb intensity and number of positive cells decreased over time, while the GPIIb/ IIIa increased in flourescent intensity and the number of positive cells. These studies indicate that T stimulation of AGP on the P surface. vWf and P4 have a transient appearance on the P surface while Ig and the 140 kD activation protein both appear to become stable components of the P plasma membrane. This technique of detecting platelet activation is a specific, sensitive, and rapid method.